Firm specific wage spread in Germany: Decomposition of regional differences in inter firm wage dispersion - Bernd Görzig; Martin Gornig; Axel Werwatz (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2006)
The purpose of this paper is to sort out firm-related differences from effects that result from different economic structures. A non-parametric decomposition is used to analyse firm level difference between the wage spread in the two major regions of unified Germany. If firm-specific effects explain wage dispersion between firms, a decomposition of the wage dispersion between firms is necessary. The decomposition can help to find out, whether the economy-wide results for different regions are due to the composition of the regional economies by industries and firm-size, or whether the differences are due to firm-specific influences, like distinctions in market power. For Germany, a considerable part of the difference in the wage spread between the East and the West can be explained by different economic structures. However, by far the greater part of the difference in the wage spread between firms in the two parts of the country results from lower wages paid by firms of the same type in East Germany compared with their counterparts in West Germany.
Keywords: L16; C14; J30; 330; Productivity; Wage Differentiation; Wage Spread; Firm Wage Levels; Wage Sharing; Non Parametric Analysis; Decomposition